An Analysis Upon Various Translating Approaches of Children’S Literature: a Review: Examining the Translation Approaches in Children's Literature (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The subject of this dissertation is children's literature and thetranslation of books for children. Various aspects of both these subjects arediscussed in order to present a comprehensive overview of this field. Adefinition and a review of the subject of children's literature are given. Theproblems of adult dominance are examined, particularly in the sections on“Asymmetry”, “Selection”, “Ambivalence” and “Manipulation”. Culturaldifferences are highlighted and their implications for the translation ofchildren's literature pointed out. and particular emphasis is placed on the commontranslation strategy of cultural and moral adaptations of the source text. Theroles of author, translator and publisher are explored. Particular emphasis isplaced on the financial side of the book industry, involving the issues of bookfails and co-productions.